Active monitoring versus an abduction device for treatment of infants with centered dysplastic hips: study protocol for a randomized controlled trial (TReatment with Active Monitoring (TRAM)-Trial) - Frederike E. C. M. Mulder; M. Adhiambo Witlox; Carmen D. Dirksen; Pieter Bas de Witte; Suzanne de Vos-Jakobs; Arno M. ten Ham; Melinda M. E. H. Witbreuk; Ralph Sakkers; Magritha (Margret); Simon G. F. Robben; TRAM-Trial Consortium; Nina M. C. Mathijssen (BMC, 2023)
Abstract Background Developmental Dysplasia of the Hip (DDH) is one of the most common pediatric orthopedic disorders, affecting 1-3% of all newborns. The optimal treatment of centered DDH is currently under debate. This randomized controlled trial aims to study the (cost-)effectiveness of active monitoring versus abduction treatment for infants with centered DDH. Methods This is a multicenter, parallel-group, open-label, non-inferiority randomized controlled trial studying the (cost-)effectiveness of active monitoring versus abduction treatment for infants with centered DDH in fourteen hospitals in the Netherlands. In total, 800 infants with centered DDH (Graf IIa-/IIb/IIc), aged 10-16 weeks, will be randomly allocated to the active monitoring or abduction treatment group. Infants will be followed up until the age of 24 months. The primary outcome is the rate of normal hips, defined as an acetabular index lower than 25 degrees on an antero-posterior radiograph, at the age of 12 months. Secondary outcomes are the rate of normal hips at the age of 24 months, complications, time to hip normalization, the relation between baseline patient characteristics and the rate of normal hips, compliance, costs, cost-effectiveness, budget impact, health-related quality of life (HRQoL) of the infant, HRQoL of the parents/caregivers, and parent/caregiver satisfaction with the treatment protocol. Discussion The outcomes of this randomized controlled trial will contribute to improving current care-as-usual for infants with centered DDH. Trial registration Dutch Trial Register, NL9714, registered September 6, 2021. https://clinicaltrialregister.nl/en/trial/29596